Decades of Shifting Trends: Arrhythmia‐Related Mortalities in the United States (1968–2021) With 2040 Projections - Mohammed Mhanna; Ahmad Al‐Abdouh; Ashraf Alzahrani; Ahmad Jabri; Abdulmajeed Al‐Harbi; Azizullah Beran; Mahmoud Barbarawi; Shareef Mansour; Paari Dominic (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Arrhythmias are a significant public health concern, and understanding their evolving patterns is vital for informed health care planning. This study explores trends and disparities in arrhythmia‐related mortality rates in the United States from 1968 to 2021, projecting up to 2040. Methods We examined national death records for cardiovascular deaths linked to arrhythmia among individuals aged 15 to 84 years, using the Centers for Disease Control and Prevention's Wide‐Ranging Online Data for Epidemiologic Research. Age‐adjusted mortality rates (AAMRs) were calculated, and trends were evaluated. Subgroup analyses were conducted on the basis of arrhythmia subtypes, age, sex, race, and geographic regions. AAMRs for 2040 were projected using Autoregressive Integrated Moving Average forecasting. Results Overall AAMRs increased from 1968 to 2021, peaking in 1988 before declining, then slightly increasing after 2006. Atrial fibrillation– or flutter‐related fatalities surpassed cardiac arrest–related deaths after 2006. Sex disparities decreased, with men maintaining higher crude mortality rates, but the gap narrowed. Younger populations witnessed an upward trend in AAMRs after 2006. Racial disparities persisted, with Black populations experiencing higher AAMRs than White populations. Conclusions This study provides insights into evolving arrhythmia‐related death. While overall AAMRs may stabilize by 2040, the projected rise in atrial fibrillation–related deaths, particularly among younger populations, necessitates further investigation. Additional research is needed to determine whether this trend reflects a true epidemiologic shift or improvements in detection and reporting. Furthermore, identifying underlying risk factors and developing targeted interventions will be crucial in mitigating AF‐related death in younger adults. Persistent racial disparities underscore the importance of equitable health care strategies.